Identification and Characterization of the Biosynthetic Gene Cluster of Thiolutin, a Tumor Angiogenesis Inhibitor, in Saccharothrix algeriensis NRRL B-24137 - Huang, Sheng; Him Tong, Ming; Qin, Zhiwei; Deng, Zixin; Deng, Hai; Yu, Yi (Anti-Cancer Agents in Medicinal Chemistry, 2015)
In this study, a new dithiolopyrrolone biosynthetic pathway was identified in Saccharothrix algeriensis NRRL B-24137, which was reported to produce a variety of dithiolopyrrolone natural products including thiolutin, a potential drug candidate for tumor angiogenesis inhibition. Bioinformatics analysis of the cluster revealed that it contains all the essential genes for holothin core biosynthesis and several other auxiliary genes. Interestingly, heterologous expression of the gene cluster in Streptomyces albus only induced the production of holomycin, implying that the gene responsible for the N4-methylation and the gene(s) involved in the formation of various acylated chains on N4 position of the holothin may locate outside the gene cluster. Incubation of holomycin with S-adenosyl-L-methionine (SAM) in the cell-free extract of Sa. algeriensis resulted in the production of thiolutin, suggesting that the N4-methyl group of thiolutin is originated from SAM, and the N4-methylation could be in the late stage of biosynthesis of thiolutin type dithiolopyrrolones. An evolution-based model for biosynthesis of thiolutin and its analogs was further proposed based on these results.
Keywords: Saccharothrix algeriensis